Quantification of lactoferrin in breast milk by ultra-high performance liquid chromatography-tandem mass spectrometry with isotopic dilution. Issue 15 (29th January 2016) - Ke, Xing; Chen, Qi; Pan, Xiaodong; Zhang, Jingshun; Mo, Weimin; Ren, Yiping
Abstract : We developed a LC-MS/MS method for quantification of human lactoferrin in breast milk based on tryptic peptides and a synthetic isotopic peptide standard. Abstract : We developed a LC-MS/MS method for quantification of human lactoferrin in breast milk based on tryptic peptides and a synthetic isotopic peptide standard. The signature peptides were obtained from tryptic breast milk. They were screened by computational prediction using Biolynx software, and confirmed by database searching after analysis using liquid chromatography-quadrupole-time-of-flight tandem mass spectrometry (LC-Q-TOF-MS). The winged isotopic-labeled signature peptide was used as an internal standard to compensate the matrix effect. The spiking recovery of human lactoferrin ranged from 92.1% to 97.5%, and the relative standard deviation (RSD) was 3.4–4.7%. The limit of detection (LOD) and limit of quantitation (LOQ) were 1 mg/100 g and 3 mg/100 g in tryptic breast milk, respectively. The present testing method was sensitive and selective, and was successfully applied to human breast milk at different lactation stages in Beijing, China. The data revealed that levels of secreted lactoferrin decreased with the extension of lactation.